Adaptation of Vibrio cholerae to Hypoxic Environments - Bueno, Emilio; Pinedo, Víctor; Cava, Felipe (Frontiers in Microbiology, 2020)
Bacteria can colonise virtually any environment on Earth due to their remarkable capacity to detect and respond quickly and adequately to environmental stressors. Vibrio cholerae is a cosmopolitan bacterium that inhabits a vast range of environments. The V. cholerae life cycle comprises diverse environmental and infective stages. The bacterium is found in aquatic ecosystems both under free-living conditions or associated with a wide range of aquatic organisms, and some strains are also capable of causing epidemics in humans. In order to adapt between environments, V. cholerae possesses a versatile metabolism characterized by the rapid cross-regulation of energy-producing pathways. Low oxygen concentration is a key environmental factor that governs V. cholerae physiology. This article reviews the metabolic plasticity that enables V. cholerae to thrive on low oxygen concentrations and its role in environmental and host adaptation.